The Effect of Administering Extract of Java Plum Ethanol (Syzygium Cumini) to the Expression of the Molecular Adhesion 1 (Icam-1) on the Model of Huvecs Preeclampsia - Siswi Wulandari; Rahma Kusuma Dewi; Supraptinigsih Supraptinigsih (Journal for Quality in Public Health, 2020)
Introduction: Preeclampsia is one of the causes of maternal mortality. In preeclampsia, endothelial dysfunction triggers the emergence of inflammatory cytokines and increases the expression of the molecular adhesion of ICAM-1. Inflammation of the preeclampsia can be controlled with the administration of anthocyanins. Java plum (Syzygium Cumini) contains anthocyanins that serve as antioxidants and anti-inflammatory. Purpose: This research aims to prove the influence of the administration of java plum (Syzygium Cumini) extracts on the expression of ICAM-1 on the model of HUVECs preeclampsia. Method: The research is conducted experimentally. It is done within the glass in a laboratory with two control groups namely negative control, three positive control, and six experimental groups (100ppm dose, 200ppm and 400ppm, incubation 1 hour, 3 hours, and 24 hours). HUVECs preeclampsia as a model of HUVECs preeclampsia within the glass. The ICAM-1 expression is used in the immunohistochemistry. The statistical analysis uses Two Way Anova test and regression test. Result: at the time of incubation of 1 hour, 3 hours, and 24 hours, there is no meaningful difference in the expression ICAM-1 (p = 0.392 > ∝). At the dose ICAM-1 of java plum, there is a meaningful difference between the positive control group with the dosage group of (p = 0.000 < ∝). Conclusion: An expression of ICAM-1 increases in preeclampsia conditions, administering java plum at a dose of 100 ppm, 200 ppm, and 400 ppm may decrease the expression of ICAM-1 in preeclampsia condition.